STUDENT ERRORS IN SOLVING MCA NUMERACY PROBLEMS ON UNCERTAINTY AND DATA CONTENT BASED ON NEWMAN'S THEORY REVIEWED THROUGH THE LENS OF ADVERSITY QUOTIENT - Hasbi Ashiddiqi; Sukoriyanto Sukoriyanto; Indriati Nurul Hidayah (EDU-MAT: Jurnal Pendidikan Matematika, 2026)
This qualitative study aims to describe the student errors made when solving numeracy problems from the Minimum Competency Assessment (MCA) on uncertainty and data content, based on Newman's theory reviewed through the lens of Adversity Quotient (AQ). AQ is categorized into five types: quitter, transition from quitter to camper, camper, transition from camper to climber, and climber. Among the five AQ categories, only three—quitter, camper, and climber—were represented among the 30 eighth-grade students from SMP Negeri 3 Genteng, Indonesia, who were considered prospective subjects in this research. Therefore, one student from each of these three AQ categories was selected as a research subject, each of whom provided complete answers but still made errors when solving the MCA numeracy problems in the uncertainty and data content. Based on the findings, students in the AQ quitter category exhibited reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. Those in the AQ camper category exhibited comprehension errors, transformation errors, process skill errors, and encoding errors. Students in the AQ climber category demonstrated comprehension errors, transformation errors, and encoding errors. Keywords: Student Errors, MCA Numeracy, Uncertainty and Data, Newman, Adversity Quotient